Heavy Metal Uptake by Indigenous Arbuscular Mycorrhizas of Nauclea orientalis L. and the Potential for Phytoremediation of Serpentine Soil - Faisal Danu Tuheteru; Asrianti Arif; Eka Widiastuti; Ninis Rahmawati (Jurnal Ilmu Kehutanan)
Effect of indigenous arbuscular mycorrhizal fungi (AMF) on growth and metal uptake of Nauclea orientalis L. plants, has been investigated. Plants were grown in greenhouse conditions on serpentine soil media without and with the AMF (Glomus sp., Acaulospora tuberculata, and mix) for two months. Lonkida roots was colonized by AMF because it was found structures of AMF: internal hyphae>external hypae>coil>vesicles>arbuscule. Colonization A. tuberculata and Glomus sp. significantly increased dry weight of root (P<0.01, r=0.810) and shoot (P<0.05, r=0.802). N. orientalis has a high dependence on inoculation of AMF (MIE>65). Transport Factor value (TF) <1 for all metals with metal uptake sequence was Fe>Mn>Ni>Cr. Glomus sp reduced Fe and Ni uptake on roots by 13% and 3%, respectively. A. tuberculata increased the uptake of all metals. Metal uptake ability was difference among types of AMF.